Dopamine modulates reward expectancy during performance of a slot machine task in rats: evidence for a 'near-miss' effect. - Winstanley, C; Cocker, P; Rogers, R (2011)
Cognitive accounts of gambling suggest that the experience of almost winning-so-called 'near-misses'-encourage continued play and accelerate the development of pathological gambling (PG) in vulnerable individuals. One explanation for this effect is that near-misses signal imminent winning outcomes and heighten reward expectancy, galvanizing further play. Determining the neurochemical processes underlying the drive to gamble could facilitate the development of more effective treatments for PG. With this aim in mind, we evaluated rats' performance on a novel model of slot machine play, a form of gambling in which near-miss events are particularly salient. Subjects responded to a series of three flashing lights, loosely analogous to the wheels of a slot machine, causing the lights to set to 'on' or 'off'. A winning outcome was signaled if all three lights were illuminated. At the end of each trial, rats chose between responding on the 'collect' lever, resulting in reward on win trials, but a time penalty on loss trials, or starting a new trial. Rats showed a marked preference for the collect lever when both two and three lights were illuminated, indicating heightened reward expectancy following near-misses similar to wins. Erroneous collect responses were increased by amphetamine and the D(2) receptor agonist quinpirole, but not by the D(1) receptor agonist SKF 81297 or receptor subtype selective antagonists. These data suggest that dopamine modulates reward expectancy following the experience of almost winning during slot machine play, via activity at D(2) receptors, and this may result in an enhancement of the near-miss effect and facilitate further gambling.